Rembrandt: Britain's discovery of the master - Seifert, Christian Tico 1968-; Black, Peter 1960-; Esposito, Donato; Dickey, Stephanie; Ripps, M. J. 1982-; Yarker, Jonathan; Elliott, Patrick 1962- (National Galleries of Scotland, 2018)
This book tells the fascinating story of Rembrandt's fame and influence in Britain. Through essays by leading scholars in the field, it explores the collecting of his artworks in the country and his impact on British artists from the 17th century to today. Including lavish images of paintings, drawings and prints and featuring British artists such as William Hogarth, James Abbott McNeill Whistler, Eduardo Paolozzi, and Ken Currie alongside the master. Exhibition: National Galleries of Scotland, Edinburgh, Great Britain (07.07. - 14.10.2018)
published ... to accompany the exhibition ... held at the Scottish National Gallery, Edinburgh from 7 July to 14 October 2018
Keywords: Rembrandt -- Harmensz van Rijn -- 1606-1669; Rezeption; Malerei; Zeichnung; Großbritannien; Ausstellungskatalog -- National Galleries of Scotland -- 07.07.2018-14.10.2018 -- Edinburgh